Bioelectric stimulation outperforms brain derived neurotrophic factor in promoting neuronal maturation - María del Pilar Diego-Santiago; María Ujué González; Esther María Zamora Sánchez; Nuria Cortes-Carrillo; Carlos Dotti; Francesc Xavier Guix; Sahba Mobini (Scientific Reports)
Abstract Neuronal differentiation and maturation are crucial for developing research models and therapeutic applications. Brain-derived neurotrophic factor (BDNF) is a widely used biochemical stimulus for promoting neuronal maturation. However, the broad effects of biochemical stimuli on multiple cellular functions limit their applicability in both in vitro models and clinical settings. Electrical stimulation (ES) offers a promising physical method to control cell fate and function, but it is hampered by lack of standard and optimised protocols. In this study, we demonstrate that ES outperforms BDNF in promoting neuronal maturation in human neuroblastoma SH-SY5Y. Additionally, we address the question regarding which ES parameters regulate biological responses. The neuronal differentiation and maturation of SH-SY5Y cells were tested under several pulsed ES regimes. We identified accumulated charge and effective electric field time as novel criteria for determining optimal ES regimes. ES parameters were obtained using electrochemical characterisation and equivalent circuit modelling. Our findings show that neuronal maturation in SH-SY5Y cells correlates with the amount of accumulated charge during ES. Higher charge accumulation (~ 50 mC/h) significantly promotes extensive neurite outgrowth and ramification, and enhances the expression of synaptophysin, yielding effects exceeding those of BDNF. In contrast, fewer charge injection to the culture (~ 0.1 mC/h) minimally induces maturation but significantly increases cell proliferation. Moreover, ES altered the concentration and protein cargo of secreted extracellular vesicles (EV). ES with large enough accumulated charge significantly enriched EV proteome associated with neural development and function. These results demonstrate that each ES regime induces distinct cellular responses. Increased accumulated charge facilitates the development of complex neuronal morphologies and axonal ramification, outperforming exogenous neurotrophic factors. Controlled ES methods are immediately applicable in creating mature neuronal cultures in vitro with minimal chemical intervention.